Can Effectuation Give Us A Better Understanding of Entrepreneurial Action in Today’s Web? Evidence from the SoundCloud Case - Benjamin, Krauth (2011)
Purpose: The purpose of this study is to gain a better understanding of the entrepreneurial realities in today’s World Wide Web (the Web). In particular, this thesis investigates whether the concept of effectuation can give us a better understanding of the entrepreneurial actions taken by entrepreneurs in today’s Web.